Two rare localizations of chondrosarcoma: cervical and thoracic spine - Sameh Sayhi; Maha Rebai; Ahmed Harbaoui; Sameh Achoura; Arij Ezzouhour Yahyaoui; Nadia Ben Abdelhafidh (Romanian Medical Journal)
Chondrosarcoma is a primary malignant bone tumor, with spinal involvement being rare. Diagnosing this condition can be challenging and typically requires histological verification. Chondrosarcoma has the potential to invade locally and spread systemically. We report the case of 32 year-old women presenting with back pain and weight loss. Magnetic resonance imaging of the spine showed a bone growth at the low cervical spine which extends to the upper dorsal spine. Histological examination showed low-grade chondrosarcoma. Given the tumor proximity to the spinal cord, an incomplete surgical excision was performed followed by radiotherapy sessions. Clinical course was marked by partial regression of the tumor process with a stability of the radiological image of the tumor after a three years follow-up. Our case is original because of the bifocality of the chondrosarcoma in two adjacent segments of the spine.